(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
This article explores the intersection of foreign language acquisition and economics education, highlighting innovative teaching methods designed to benefit economics students. It discusses the increasingly vital role of multilingual proficiency in the global economy and addresses the limitations of traditional language teaching methodologies in meeting the specific needs of students pursuing economics. The article outlines several forward-thinking approaches, including Content and Language Integrated Learning (CLIL), Project-Based Learning (PBL), professional language exchange programs, gamification, technology-enhanced learning, and the flipped classroom model. These methods aim not only to enhance foreign language proficiency but also to deepen students’ understanding of economic concepts in a global context. By integrating content knowledge with language learning, these approaches offer a more engaging, relevant, and practical educational experience, preparing students for the complexities of the global economy